OPTIMIZATION OF PHARMACO-PHYSIOTHERAPEUTIC METHODS IN THE TREATMENT OF ATOPIC DERMATITIS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the optimization of pharmacological and physiotherapeutic methods in the treatment of atopic dermatitis in children. Based on the results of the study, the most effective therapy methods are identified.